Design and testing of an automated high-throughput computer vision guided waterjet knife strawberry calyx removal machine. (October 2017) - Lin, John; Holmes, Maxwell; Vinson, Robert; Ge, Canran; Pogoda, Frank C.; Mahon, Luke; Gentry, Ryan; Seibel, Gary E.; Chen, Xin; Tao, Yang
Abstract: An automated high-speed strawberry calyx removal machine was designed, built, tested, and evaluated. The three main components of the machine consisted of 1) a strawberry loading and orientation conveyor, 2) a color-based machine vision section for strawberry feature identification, and 3) a synchronized multi-waterjet knife calyx removal system. An overview of the machine as well as a description of the working principles of each component is included. A full-scale model of this machine was evaluated through a 12-week pilot study, during which the machine processed over 70 metric tons of strawberries. Results indicated that the machine could produce an average calyx-free strawberry weight yield of 49.6 percent at a rate of 2270 kg/hr. Furthermore, it was seen that strawberry size had a significant effect on machine efficacy. Highlights: An automated waterjet based strawberry calyx removal machine is designed and tested. A quick method to orient, singulate, and stabilize conical strawberries for calyx removal is evaluated. The machine produced an average weight yield efficacy of 49.6 percent at a rate of 2270 kg/hour.